2021
DOI: 10.1021/acs.energyfuels.1c00659
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanoparticle-Based Formulation to Mitigate Asphaltene Deposition

Abstract: Asphaltene precipitation and subsequent deposition are challenging problems that hinder continuous crude oil production worldwide. Although this is a long-standing and complex problem and many efforts have been devoted to its mitigation, there is no commercial "one size fits all" type of product to reduce asphaltene deposition to date. In this work, a systematic investigation was conducted to assess the performance of commercial asphaltene inhibitors that are commonly used to disperse asphaltenes upon precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…These nanoparticles are designed to have nanometer-sized dimensions and are intended to interact with asphaltenes, inhibiting their aggregation and deposition. They can be synthesized using various techniques, and their performance is based on specific surface and chemical properties [214,215].…”
Section: Outlook and New Technologiesmentioning
confidence: 99%
“…These nanoparticles are designed to have nanometer-sized dimensions and are intended to interact with asphaltenes, inhibiting their aggregation and deposition. They can be synthesized using various techniques, and their performance is based on specific surface and chemical properties [214,215].…”
Section: Outlook and New Technologiesmentioning
confidence: 99%
“…In principle, chemical inhibitors can inhibit asphaltene precipitation and reduce the amount of asphaltene deposit at different level. So far, the reported chemical inhibitors can be classified as small molecules, 14–16 nanoparticles, 17–20 and polymers 21–24 . Small molecules mainly include natural fatty acids 14 and synthetic surfactants 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…the presence of asphaltene in crude can lead to significant operational and production issues (Chala et al 2018). Hence, serious research efforts have been made to investigate its effects and possibilities of mitigating its effects (Khaleel et al 2020;Enayat et al 2021). Asphaltene deposition after CO 2 injection in conventional oil reservoirs has been the subject of several investigations (Enayat et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, serious research efforts have been made to investigate its effects and possibilities of mitigating its effects (Khaleel et al 2020;Enayat et al 2021). Asphaltene deposition after CO 2 injection in conventional oil reservoirs has been the subject of several investigations (Enayat et al 2021). Studies have shown that an increase in pressure below CO 2 minimum miscibility pressure (MMP) causes asphaltene deposition in sandstone to increase, while above CO 2 MMP an increase in pressure causes asphaltene deposition to decrease (Soroush et al 2014).…”
Section: Introductionmentioning
confidence: 99%